2010
DOI: 10.1016/j.ejcnurse.2009.11.008
|View full text |Cite
|
Sign up to set email alerts
|

Wound Management and Restrictive Arm Movement Following Cardiac Device Implantation — Evidence for Practice?

Abstract: We discuss the reasons behind these gaps in the evidence base and support the idea that nursing education has not placed enough emphasis on how to critically appraise research. This accounts for the very small proportion of nurses that get involved in conducting research and generating guidelines. Additionally, we argue that nurses can play a key role in identifying and addressing research questions that lead to improved patient outcome. Thus, we support proposals to enhance nurses' opportunities to pursue aca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 35 publications
1
1
0
Order By: Relevance
“…This low practice level may have relevance to low knowledge levels in addition to increased number of patients and workload. These findings agreed with Bavnbek et al ( 2010) whose study on wound management and restrictive arm movement following cardiac device implantation, found that certain aspects of established practice are based on tradition rather than evidence and nurses are lacking knowledge in some aspects of care giving. Accordingly, they concluded that nurses should play a key role in identifying and addressing research questions that lead to improved patient outcomes.…”
Section: Discussionsupporting
confidence: 88%
“…This low practice level may have relevance to low knowledge levels in addition to increased number of patients and workload. These findings agreed with Bavnbek et al ( 2010) whose study on wound management and restrictive arm movement following cardiac device implantation, found that certain aspects of established practice are based on tradition rather than evidence and nurses are lacking knowledge in some aspects of care giving. Accordingly, they concluded that nurses should play a key role in identifying and addressing research questions that lead to improved patient outcomes.…”
Section: Discussionsupporting
confidence: 88%
“…11 However, after the first year following implantation, limitations become permanent and are not self-resolved. 12,13 Although studies have shown that early mobilization after CIED implantation is safe, [14][15][16][17] some physicians habitually prefer to temporarily immobilize the arm with a sling or restrict arm movements above the shoulder level. 18,19 Also, patients may extend this period of their own accord to avoid the risk of device malfunction.…”
Section: Introductionmentioning
confidence: 99%